2022
DOI: 10.1007/s00246-022-02844-w
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease Arab Initiative [Kawarabi]: Establishment and Results of a Multicenter Survey

Abstract: Studies on Kawasaki disease (KD) in Arab countries are scarce, often providing incomplete data. This along with the benefits of multicenter research collaboratives led to the creation of the KD Arab Initiative [Kawarabi] consortium. An anonymous survey was completed among potential collaborative Arab medical institutions to assess burden of KD in those countries and resources available to physicians. An online 32-item survey was distributed to participating institutions after conducting face validity. One surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 41 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…However, previous research reported Asian ethnicity as a KD risk factor in Hawaii (50.4/100 000 children <5 years of age)1 and in other Asian populations worldwide 6. In line with previous work, we observed that most patients presented with typical (complete) KD7 and there were a higher number of cases in winter similar to seasonal peaks in Japan,1 Saudi Arabia4 and the USA 1. Cardiac involvement is the most important feature of KD and CAA developed in ~25% of untreated patients 1.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…However, previous research reported Asian ethnicity as a KD risk factor in Hawaii (50.4/100 000 children <5 years of age)1 and in other Asian populations worldwide 6. In line with previous work, we observed that most patients presented with typical (complete) KD7 and there were a higher number of cases in winter similar to seasonal peaks in Japan,1 Saudi Arabia4 and the USA 1. Cardiac involvement is the most important feature of KD and CAA developed in ~25% of untreated patients 1.…”
supporting
confidence: 90%
“…The recently proposed KD Arab Initiative (Kawarabi) should provide future data to help improve the diagnosis, care and outcomes of children with KD across different Arab nations and ethnicities. 7…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawasaki Disease Arab Initiative (Kawarabi) was established to identify the impact of KD on cardiovascular health in the Arab world and address the challenges faced by physicians caring for children with KD in that region [4] . This survey shows signi cant heterogeneity in the care for children with KD between large, industrialized cities and rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, according to literature from Arab nations, there are limited data on the resources available for acute management and lifelong surveillance of KD. 6,7,11,12 The Kawasaki Arab Initiative (Kawarabi) established in 2021 13 is a multicenter consortium that fosters collaboration between KD experts and maintains an active registry of KD patients to understand the epidemiology of KD and disease burden in the Arab world, including mortality and long-term morbidities in children and adults. This initiative also seeks to raise awareness of KD in the medical community and among the general population.…”
Section: Introductionmentioning
confidence: 99%